The Effectiveness of Logotherapy on Body Dysmorphic Disorder and Self-Esteem in Women Undergoing Cosmetic Surgery - Zohrei, Moslem; Salajegheh, Mahsa; Jodaki, Tahereh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to investigate the effectiveness of logotherapy on body dysmorphic disorder and self-esteem in women undergoing cosmetic surgery. Methodology: The research employed a quasi-experimental design with control and experimental groups using pretest-posttest methodology. The target population consisted of all women in Shiraz who had undergone at least one cosmetic surgery. A purposive sampling method was used to select 30 participants, who were then randomly assigned to experimental and control groups. Data were collected using the Body Dysmorphic Disorder Questionnaire developed by Phillips et al. (1997) and the Rosenberg Self-Esteem Scale (Rosenberg, 1965). The experimental group participated in eight sessions of logotherapy. Data were analyzed using analysis of covariance (ANCOVA). Findings: The results of one-way ANCOVA showed a statistically significant difference between the experimental and control groups in both dependent variables after controlling for pretest scores. Logotherapy significantly reduced symptoms of body dysmorphic disorder (F(1, 27) = 68.37, p < .001, η² = .707) and significantly increased self-esteem (F(1, 27) = 67.10, p < .001, η² = .713) in the experimental group compared to the control group. Conclusion: Therefore, it can be concluded that prior to performing cosmetic surgeries, this type of therapy can be utilized to enhance women’s satisfaction with their appearance and body, as well as to improve their self-esteem.